Mathematical Modeling of Air Pollution Near Roads and Assessment of Disease Risk in People Exposed to Vehicle Emissions - Kuznetsov, V. M.; Biliaieva, V. V.; Berlov, O. V.; Zvonarova, O. V.; Mashykhina, P. B. (Science and Transport Progress, 2025)
Purpose. The work is aimed at developing a numerical 2D model that allows for the rapid calculation of the absorption of polluted air near the road. A fast CFD model should take into account meteorological parameters, a suction pipe near the road to remove polluted air, and the rate of toxic gas emissions. Methodology. The developed model is based on the potential flow equation and the pollutant mass transfer equation. The potential flux equation is used to calculate the wind flow near the road in the case of a suction pipe. The Liebman numerical integration method was used to solve the potential flow equation. To solve the convective-diffusive dispersion equation, an implicit variable-triangular difference scheme was used. The numerical integration is carried out using a rectangular difference grid. The porosity method (“marker method”) was used to create the shape of the complex computational zone. Toxic gas emissions from a car were modeled using the Dirac delta function for a point source. Findings. The developed numerical 2D model takes into account the main physical factors that affect the process of dispersion of pollutants near the road. The model takes into account the influence of a car and a suction pipe located near the road to remove polluted air. On the basis of the developed numerical models, a computational experiment was conducted to assess the impact of the use of a suction pipe on local air pollution near the road. Originality. The developed numerical model allows to calculate a two-dimensional flow pattern near the road, where such a mitigation measure as a suction pipe is used. The model allows for quick calculations of air pollution, taking into account the impact of the protective barrier. Based on the data on the distribution of the concentration of a non-hazardous substance, the risk of disease in a person exposed to vehicle emissions was determined. Practical value. The software implementation of the developed numerical model was carried out, and a computational experiment was conducted to illustrate the effectiveness of using the model to solve applied problems. The results of the numerical experiment are presented.